Devilfish bone char, an alternative material to be used as bioanode in microbial fuel cells - Aguilera Flores, Miguel Mauricio; Avila Vázquez, Verónica; Medellín Castillo, Nahum Andrés (Frontiers in Sustainability, 2022)
This work aimed to evaluate the devilfish bone char as an alternative material to be used as a bioanode in a microbial fuel cell (MFC) applied in bioenergy production from the pantoprazole biodegradation. The devilfish is an invasive species in Mexico and other countries, so its control and eradication are based on the integral use of its biomass. In addition, the bones are unusable waste and could be used as a raw material to manufacture the bioanode. Two MFCs with an anaerobic anode single chamber of 125 mL were operated independently using the fabricated bioanode and the carbon felt (conventional anode). Both MFCs were fed with 1 g/L of pantoprazole as substrate with a chemical oxygen demand (COD) of 210 ± 1.3 mg/L and 1.2 g of soil as inoculum. The two MFCs were characterized electrochemically, and the COD removal percentage was measured as an indicator of the pantoprazole biodegradation. The results showed that the MFC operated with the bioanode had a better performance than the conventional anode, since it reached a maximum power density of 1.22 mW/m2, being 156% higher than carbon felt. These values were consistent with the COD removal percentages reached in 10 days with values of 47.17 ± 0.23 and 43.34 ± 0.41%, respectively. Therefore, these findings provide a low-cost alternative carbonaceous material for the sustainable construction of MFC applied to produce bioenergy from the biodegradation of pharmaceutical products.